Flight : Alberta’s early learning and care framework : play, participation, and possibilities - Makovichuk, Lee; Hewes, Jane; Lirette, Patricia; Thomas, Nancy (My University, 2014)
Flight is a curriculum framework intended to guide the significant work of early learning and child care educators with young children (ages 0 – before 6 years) and their families in centre-based child care and family day home settings. This is a flexible framework for thinking about how children learn and experience their worlds, as well as a guide that fosters strong early childhood communities. Children’s play is central to this curriculum framework as an active, exploratory, creative, expressive process, deeply embedded in children’s everyday experiences and through which children participate in, learn about, and actively make sense of the world.
Keywords: early childhood education; curriculum framework